USING READING GUIDANCE TECHNIQUE TO IMPROVE STUDENTS’ READING SKILL WITH NARRATIVE TEXT - Mamarodia, Merisa; Rinny Rorimpandey; Tirza A. Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research is to find out if the using of reading guidance technique can improve students’ reading skill with narrative text. This is a quantitative study using pre-experimental group design. The subjects of this study were 21 students from SMP Negeri 2 Tondano class VII and it divided to A and B group. Based on the data obtained, the highest score in Experimental Group is 100 and the lowest is 70, while the highest Control Group score is 40 and the lowest is 10 with the mean score in the Experimental Group 83.33 and the mean score in Control Group is 25.23. Based on data obtained the students reading skill can be improved by using reading guidance technique through narrative text.